Topological Lifshitz transitions - Volovik, G.E. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2016)
Different types of Lifshitz transitions are governed by topology in momentum space. They involve the topological transitions with the change of topology of Fermi surfaces, Weyl and Dirac points, nodal lines, and also the transitions between the fully gapped states.